'Ergopaedics': the future of ergonomics in orthopaedics. (2nd November 2021) - Neal-Smith, Gregory; Butler, Katherine; Patel, Bhavi; Huntley, Daniel; Wood, Alexander
Abstract : Ergonomics is the scientific study of people and their working conditions, aiming to improve effectiveness. Improved ergonomics of orthopaedic theatres and equipment would reduce the risk of occupational injury and help to encourage more women into an underrepresented specialty.